Ultrastrong eutectogels engineered via integrated mechanical training in molecular and structural engineering - Chenggong Xu; Ao Xie; Haiyuan Hu; Zhengde Wang; Yange Feng; Daoai Wang; Weimin Liu (Nature Communications)
Abstract Ultrastrong gels possess generally ultrahigh modulus and strength yet exhibit limited stretchability owing to hardening and embrittlement accompanied by reinforcement. This dilemma is overcome here by using hyperhysteresis-mediated mechanical training that hyperhysteresis allows structural retardation to prevent the structural recovery of network after training, resulting in simply single pre-stretching training. This training strategy introduces deep eutectic solvent into polyvinyl alcohol hydrogels to achieve hyperhysteresis via hydrogen bonding nanocrystals on molecular engineering, performs single pre-stretching training to produce hierarchical nanofibrils on structural engineering, and fabricates chemically cross-linked second network to enable stretchability. The resultant eutectogels display exceptional mechanical performances with enormous fracture strength (85.2 MPa), Young’s modulus (98 MPa) and work of rupture (130.6 MJ m−3), which compare favorably to those of previous gels. The presented strategy is generalizable to other solvents and polymer for engineering ultrastrong organogels, and further inspires advanced fabrication technologies for force-induced self-reinforcement materials.